Soybean biochar as highly efficient adsorbent for ofloxacin from aqueous and CO2 from gaseous phase: Mathematical modelling and regeneration studies - Vaishnavi Gomase; Tejaswini Rathi; Aparna Muley; D. Saravanan; Ravin Jugade (Cleaner Chemical Engineering)
This study seeks to repurpose soybean biowaste by activating and pyrolyzing it, resulting in phosphoric acid-treated soybean biochar (PTSB). The novelty of this approach lies in its ability to effectively remove both aqueous and gaseous pollutants, making it a versatile solution for environmental remediation. By transforming agricultural waste into a high-value material, this method not only promotes sustainability but also offers a dual-purpose adsorbent capable of addressing a broader range of contaminants than traditional adsorbents. This innovative process represents a significant advancement in both waste valorization and pollution control. With a substantial surface area of 289.82 m² g⁻¹, this carbonized biochar effectively adsorbs ofloxacin (OFX) from water and captures CO₂ in its gaseous form. Characterization of PTSB was conducted using various techniques. Batch adsorption experiments were optimized using response surface methodology (RSM), resulting in over 95 % adsorption efficiency. Isotherm and kinetics studies indicated that the adsorption process adheres to Langmuir adsorption isotherm and pseudo-second-order kinetics. Notably, a significant observation was made regarding the increase in adsorption with rising temperature. The maximum adsorption capacities (qm) at temperatures of 303 K, 313 K, and 323 K were determined to be 96.83 mg g−1, 147.56 mg g−1, and 201.82 mg g−1, respectively, as derived from the Langmuir adsorption isotherm. Examination of CO2 sequestration at various temperatures demonstrated highest adsorption recorded at 273 K, reaching 49.96 mL g−1. Furthermore, Qst values for CO2 removal were consistently below 40 kJ mol−1, indicating a physisorption process. Furthermore, mathematical modeling techniques were applied to forecast the OFX breakthrough curve and assess various removal approaches. The results of this research aid in the advancement of efficient remediation techniques aimed at reducing the environmental repercussions of OFX contamination. The study investigated the regeneration of PTSB and the degradation of OFX using reagents, UV, and gamma radiation.